Advancements in Diagnosing Talaromycosis: Exploring Novel Strategies and Emerging Technologies - Yihui Wang; Xiaoyue Wang; Liyan Xi; Sha Lu (Journal of Fungi)
Talaromycosis (TM) is an invasive fungal infection caused by Talaromyces marneffei (T. marneffei). It has high morbidity and mortality rates, particularly among immunocompromised people. Globally, approximately 17,300 cases and 4900 deaths are reported annually. TM often has vague clinical signs with limited current tests, leading to misdiagnosis, incorrect treatments, or the long-term use of expensive antifungal drugs, which raises healthcare costs and patient risks. Although accurate diagnosis is key for starting the right antifungal therapy and improving outcomes, there are not enough reliable and fast tests. Recent progress with monoclonal antibodies (mAbs) that have high specificity for antigens may boost diagnostic accuracy and cut misdiagnosis rates. This review explores current ways to diagnose TM, including culture, histopathology, and molecular methods such as polymerase chain reaction (PCR) and antigen detection. We also discuss the merits and weaknesses of each method and highlight how mAbs may help diagnose TM. We searched PubMed, Web of Science, and Google Scholar for English-language papers (1990—1 January 2025) using “Talaromycosis” OR “Talaromyces marneffei” plus diagnostic terms (‘diagnosis’, ‘molecular diagnostics’, ‘monoclonal antibody’, ‘lateral flow’, ‘antigen detection’, and ‘fungal diagnosis’). After deduplication and relevance screening, studies with original data or substantive discussion on T. marneffei diagnostics or mAb development were retained to inform this narrative review.